2017
DOI: 10.1088/1742-6596/860/1/012030
|View full text |Cite
|
Sign up to set email alerts
|

Innovative research of plasma physics for life sciences

Abstract: Abstract. In medicine, cold atmospheric plasma (CAP) for the medical treatment is a new field in plasma application, called plasma medicine. CAP contains mix of excited atoms and molecules, UV photons, charged particles as well as reactive oxygen species (ROS) and reactive nitrogen species (RNS). Typical species in air-CAPs are O 3 , OH, N x O x , and HNO x . The current developments in this field have fuelled the hope that CAP could be an interesting new therapeutic approach in the treatment of cancer. CAP ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…A number of reviews have demonstrated the efficacy of CP in medicine and dentistry (Boonyawan, ; Laroussi et al ., ; Weltmann & von Woedtke, ; Xu et al ., ). According to Heinlin et al .…”
Section: Introductionmentioning
confidence: 99%
“…A number of reviews have demonstrated the efficacy of CP in medicine and dentistry (Boonyawan, ; Laroussi et al ., ; Weltmann & von Woedtke, ; Xu et al ., ). According to Heinlin et al .…”
Section: Introductionmentioning
confidence: 99%
“…A body of O-dominated cold plasma is formed between the upper and bottom electrodes after the electrodes are triggered and controlled oxygen gas is fed into the reactor chamber. As mentioned above, the plasma is composed of charged particles, such as ions and electrons, neutrals and ROS, as well as ultraviolet light (which also assists in the ROS production), as diagonalized in various experiments (such as Steinbruchel et al, 1986, as a very early one), including those by the members of the current authros (Boonyawan, 2017, Kosumsupamala et al, 2022. As the bottom electrode is biased with -500 V, the ions have a higher concentration near the bottom electrode (above which the seeds are placed) than near the upper electrode (while electrons have the opposite concentration distribution), as illustrated in Fig.…”
Section: Discussionmentioning
confidence: 99%